Cerebral schistosomiasis: Case series from Qatar. (September 2019) - Zaqout, Ahmed; Abid, Fatma Ben; Murshed, Khaled; Al-Bozom, Issam; Al-Rumaihi, Ghaya; Al Soub, Hussam; Al Maslamani, Muna; Al Khal, Abdullatif
Highlights: This report describes three challenging cases in which patient with tumor-like brain lesion had a diagnosis of neuroschistosomiasis. In patients presenting with seizures, especially migrants and returning travelers from an endemic area, neuroschistosomiasis should be suspected. Neuroimaging showing a characteristic nodular pattern of enhancement should raise the suspicion of neuroschistosomiasis. Appropriate investigations must be performed and treatment can minimize the resultant tissue damage and prevent chronic sequelae. Abstract: Schistosomiasis is the third most widespread devastating parasitic disease worldwide and has a high mortality burden. Neuroschistosomiasis is one of the rare and most severe clinical presentations of the disease. It is caused by granuloma formation around eggs that lodge in the central nervous system, with Schistosoma japonicum usually causing most reported cerebral disease. Three unusual presentations of schistosomiasis in Qatar are described herein. The three patients were young males who presented with seizures and tumor-like lesions on brain imaging. The diagnosis was confirmed by biopsy, which showed necrotizing granulomas containing Schistosoma eggs. These cases raise awareness of neuroschistosomiasis as a potential cause of tumor-like brain lesions in migrants and returning travelers from endemic areas.